PENGEMBANGAN BUKU CERITA BERGAMBAR BERBASIS DIGITAL PADA PEMBELAJARAN IPAS DI SEKOLAH DASAR - Islamiati, Asti; Akhmad Nugraha; Muhammad Rijal Wahid Muharram (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The lack of understanding among students regarding the human digestive system material in elementary schools is due to the limitations of teaching resources used by educators. The aim of this research is to develop a digital-based illustrated storybook that can be used as teaching material or reading content on the human digestive system within the independent curriculum framework. This study employs the ADDIE model, which includes (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation stages. Data collection techniques include interviews, document studies, expert validation, and response questionnaires. The results of media expert validation show an average percentage of 93% with a very feasible criterion, illustration validation results show an average percentage of 75% with a feasible criterion, material expert validation results show an average percentage of 88% with a very feasible criterion, and language expert validation results show an average percentage of 82% with a very feasible criterion. The trial was conducted twice; the first trial results from student response questionnaires show an average percentage of 97% with a very good criterion, while educator response questionnaires show an average percentage of 80% with a good criterion. In the second trial, student response questionnaires show an average percentage of 99% with a very good criterion, while educator response questionnaires show an average percentage of 85% with a very feasible criterion. Thus, the developed Digital-Based Illustrated Storybook on the Digestive System is very feasible and highly suitable for use in elementary schools.